Accuracy of recording of malaria rapid diagnostic test results in Uganda - Ssewante, Nelson; Namuganga, Jane Frances; Katahoire, Anne; Musoke, Jenipher; Mutesi, Noel; Humes, Michael; Griffith, Kevin; Aponte, John J.; Soebiyanto, Radina; Cooper, Shawna; Agaba, Bosco; Opigo, Jimmy; et al. (Malaria journal, 2025)
Background Malaria rapid diagnostic tests (RDTs) have been critical in promoting the rational use of antimalarials and strengthening malaria surveillance. However, the accuracy of routinely reported RDT results in Uganda remains unclear. The study’s objective was to measure the level of agreement between healthcare workers (HCWs) and an external panel’s RDT results among lower-level public health facilities in Busoga and Lango regions, Uganda. Methods A prospective study was conducted in 16 public health facilities in four purposively selected districts in Uganda. At each study site, images of all RDTs were taken as soon as the HCW had finished interpreting the test results and uploaded into HealthPulse (Audere, Seattle, WA USA), a digital RDT reader. Corresponding patient data was captured from the outpatient department (OPD) register, including demographics and RDT test results. RDT images were sent to a trained, external panel for interpretation. Cohen’s kappa statistic (κ) was used to determine agreement. The associations between characteristics of health facilities, HCWs and RDTs and the level of agreement were analysed using meta-analytical approaches. Results From June to November 2023, 40,049 RDT images were captured, of which 37,137 (92.7%) were included in the analysis. Overall, the test positivity rate based on OPD records was 61.8%. The overall agreement was strong (κ 0.81, 95% confidence interval [CI] 0.76, 0.85). Where disagreement occurred, HCWs misrecorded more RDT results as positive (7.2%) than negative (1.9%). Agreement was higher in Busoga (κ 0.86, 95% CI 0.83, 0.88) compared to Lango (κ 0.78, 95% CI 0.75, 0.81). Lower agreement levels were also associated with certain RDT products and RDTs with faint lines. Conclusion The study found a strong level of agreement between HCWs' RDT results and an external panel. However, significant proportions of results were misrecorded as positive or negative, particularly in the Lango region. Targeted interventions, such as RDT validation exercises and tailored refresher training, are recommended to enhance RDT reporting accuracy in Uganda.